In vitro inhibitory effects of some acetophenone derivatives on some metabolic enzymes and molecular docking - Taslimi, Parham; Taslimi, Parham (Wiley-V C H Verlag Gmbh, 2020)
In this study, the acetophenone derivatives1-6were found to be effective inhibitor molecules for alpha-glycosidase, human carbonic anhydrases I and II (hCA I/II), and acetylcholinesterase (AChE), withK(i)values in the range of 167.98 +/- 25.06 to 304.36 +/- 65.45 mu M for alpha-glycosidase, 555.76 +/- 56.07 to 1,043.66 +/- 98.78 mu M for hCA I, 598.63 +/- 90.04 to 945.76 +/- 74.50 mu M for hCA II, and 71.34 +/- 11.25 to 143.75 +/- 31.27 mu M for AChE, and IC(50)values of 73.65-101.13 mu M for tyrosinase. In the last step, molecular docking calculations were performed to compare the biological activities of molecules with their docking scores in these enzymes. The interactions of the studied molecules against human alpha-galactosidase (PDB ID: 1R47), hCA I (PDB ID: 3LXE), human AChE (PDB ID: 4M0E), hCA II (PDB ID: 5AML), and human tyrosinase (PDB ID: 5M8Q) were examined to compare the biological activity values. The ADME/T analysis (adsorption, distribution, metabolism, and discharge) was then performed for the future use of these molecules as drugs.
Keywords: Acetophenone; Acetylcholinesterase; Carbonic Anhydrase; Molecular Docking; Alpha-Glycosidase